The Associated Factors Due Satisfaction of BPJS Services in Hospital Hikmah of Makassar - Andi Nailah Amirullah; Yuliani; Nurhidayat (MIRACLE Journal Of Public Health, 2021)
Health care facilities are expected to provide satisfactory services in hospitals. Have not being able to provide the maximum service expected by service users is the problem often faced by hospitals. Where the main assessment of the quality of health services is patient satisfaction. Based on a preliminary study at the RS Hikmah Makassar, it was found that more people were dissatisfied with health services. The purpose of this study was to find out the factors related to BPJS service satisfaction in BPJS Health participants at Hospital Hikmah of Makassar. The research design used Cross-Sectional. The population is 426 people. The sample in this study were some participants who used BPJS cards in Hospital Hikmah Of Makassar as many as 81 people, taking samples by purposive sampling technique. This research was conducted in May - June 2019. Data was collected with Questioner and analysed with the Chi-Square test. The results showed that there was a relationship between BPJS administration services, doctors and nurses services, supporting examination services and drug services with the satisfaction of BPJS services for BPJS Health participants in Hospital Hikmah of Makassar. The study suggested to health workers provide patients with a more friendly attitude and attention to patients recipients of health services.